Efeitos do estresse por separação maternal no comportamento de camundongos machos e fêmeas pré-púberes wild-type ou CX3CR1-GFP heterozigotos - Beatriz Campos Codo (2023)
Chronic early-life stress leads to physiological and behavioral alterations, with some of these changes persisting into adolescence or adulthood. Postnatal stress exposure is a risk factor in the development of various neuropsychiatric disorders, such as anxiety, mood, and eating disorders. Brain development and stress response involve the integration of diverse systems beyond the nervous system and cell types beyond neurons. Glial cells play a significant role in maintaining homeostasis. Microglia play multiple fundamental roles during neurodevelopment. A key player in microglia-neuron communication is the CX3CR1 receptor, present in microglia. The heterozygous CX3CR1-GFP animal (CX3CR1-GFP+/-) is widely used in research to study stress responses in microglial morphology and functionality. However, little is known about the behavioral effects of maternal separation stress in these animals and the comparison of these effects between these animals and wild-type animals. In this study, we exposed CX3CR1GFP+/- animals and wild-type animals, both males and females, to 180 minutes of maternal separation early in life for 13 days. The animals underwent exploratory, anxiety-like, and depressive-like behavioral tests in early adolescence. We observed that CX3CR1-GFP+/- animals exhibited higher exploratory behavior and anxiety-like behavior than wild-type animals. Animals that experienced maternal separation displayed lower depressive-like behavior than animals that did not were submitted stress. Furthermore, males exhibited higher anxiety-like behavior and lower exploratory behavior than females. We did not find any differences between any groups in the post-hoc test. This shows we need to increase the number of animals per group. Our findings suggest that maternal separation led to a subtle resilience effect in prepubertal mice; that CX3CR1-GFP+/- animals exhibit distinct behavioral phenotypes from wild-type animals that should be considered when designing experiments; and that prepubertal males and females display sexually dimorphic anxiety-like behavior. Further studies are needed to better understand how these factors contribute to the observed behavioral phenotypes.